Siklus Hidup Kupu-Kupu Graphium agamemnon L. (Lepidoptera: Papilionidae) di Kampus I Universitas Islam Negeri Syarif Hidayatullah Jakarta - FITRIANA, NARTI; MAULIDIA, NUR AZIZAH; WIJAYANTI, FAHMA (Jurusan Biologi FMIPA Universitas Riau, 2016)
Graphium agamemnon butterfly often observed flying, mating and laying eggs on glodokan plants(Polyalthia longifolia Sonn.) that planted as greening along the campus corridor in UIN SyarifHidayatullah Jakarta. This study was conducted to examine the use of plants as well glodokan butterflylife cycle of G. agamemnon using survey method. Observations were made in artificial semi-naturalenclosure that was placed in the room. Parameter observations include the timing and place ofoviposition, morphology and length of each stage until imago. Based on observations, G. agamemnon puttheir eggs on the lower sides of young leaves (80%) with 88.30 ± 34.74 cm distance above the groundlevel at 9:00 up to 10:58 pm. The life cycle of G. agamemnon take place during 31-38 days, consisting ofegg stage for 2-3 days (diameter egg shell 1.233 ± 0.101 mm), first instar larvae (L1) for 2-4 days (thelength of the larvae 4.624 ± 0.673 mm) , L2 for 2-4 days (9.387 ± 2.028 mm), L3 for 1-4 days (14.883 ±2.112 mm), L4 for 2-4 days (26.036 ± 3.983 mm), L5 for 3-8 days (37.948 ± 4.280 mm), prepupa for 1-2days (32.991 ± 1.527 mm) and pupa for 12-15 days (32.532 ± 1.150 mm). Each stage has a differentmorphology. Sex ratio of male: female was 3: 2.Keywords: life cycle, butterflies G. agamemnon, glodokan